Coordination of financial management of development of agricultural machine building enterprises - Kotkalova-Lytvyn, Inna (Skhid, 2020)
The paper identifies the specifics of the activities of agricultural machinery, which is focus on areas of agricultural production, and location is associated with the zonal specialization of agriculture. An approach to coordinating the management of financial support for the development of agricultural machinery enterprises has been developed based on a model of dynamic programming for conditional and unconditional optimization, which allows coordinate the distribution of financial flows between development projects with limited financial support and achieving maximum expected efficiency. It is proved that the coordination of financial flows according to this distribution will ensure the achievement of the maximum expected economic effect from the construction of a service center for the repair of agricultural machinery and supply of agricultural machinery to PJSC "Elworthy".